АСИНХРОННІ ГЕНЕРАТОРИ В АВТОНОМНИХ ДЖЕРЕЛАХ ЖИВЛЕННЯ ЗВАРЮВАЛЬНОЇ ДУГИ. СТАН І ПЕРСПЕКТИВИ - Мазуренко, Л.І.; Джура, О.В.; Шихненко, М.О.; Білик, О.А. (Інститут електродинаміки Національної академії наук України, 2024)
The article is aimed at generalizing the results of the study of asynchronous generators (AG) of autonomous welding arc power sources (AWPS) obtained in the Department of Electromechanical Systems of the Institute of Electrodynamics of the NASU. The proposed classification of AG of autonomous welding systems is considered, mathematical models are developed, the results of computational and experimental studies of such systems with AG with capacitor excitation and an uncontrolled rectifier, in the DC circuit of which high-frequency inverters, pulse-width regulators or half-bridge inverters are connected, as well as generators with valve and valve-capacitor excitation. The design features and experimental samples of welding arc power sources with AG are considered. The directions of further research are determined. Ref. 42, fig. 5.